2021 Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition (DATE) 2021
DOI: 10.23919/date51398.2021.9474081
|View full text |Cite
|
Sign up to set email alerts
|

Neuron Fault Tolerance in Spiking Neural Networks

Abstract: The error-resiliency of Artificial Intelligence (AI) hardware accelerators is a major concern, especially when they are deployed in mission-critical and safety-critical applications. In this paper, we propose a neuron fault tolerance strategy for Spiking Neural Networks (SNNs). It is optimized for low area and power overhead by leveraging observations made from a largescale fault injection experiment that pinpoints the critical fault types and locations. We describe the fault modeling approach, the fault injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 20 publications
3
31
0
Order By: Relevance
“…Theoretically, high fault tolerance to noisy data and low power consumption during computations are both essential factors for real-time information processing on neuromorphic chips [51], [65]. Our analysis revealed that SNNs trained by the synergistic learning approach exhibit strong robustness to various types of noise.…”
Section: Joint Decision Framework For Snnsmentioning
confidence: 88%
“…Theoretically, high fault tolerance to noisy data and low power consumption during computations are both essential factors for real-time information processing on neuromorphic chips [51], [65]. Our analysis revealed that SNNs trained by the synergistic learning approach exhibit strong robustness to various types of noise.…”
Section: Joint Decision Framework For Snnsmentioning
confidence: 88%
“…Symptom detectors that detect some anomaly in intermediate nodes, i.e., high neuron activation, are proposed in [11], [21]- [23]. Selective Triple Modular Redundancy (TMR) applied to the most critical neural network layers is proposed in [22], [24], [25]. Algorithmic-based error detection and correction methods using checksum arithmetic are discussed in [13], [26]- [29].…”
Section: Prior Art On Testing Ai Hardware Acceleratorsmentioning
confidence: 99%
“…Every node carries an identification corresponding to its x and y address in the mesh, and its color indicates the respective layer in the network. Nodes (5,4) and (6,4) are extra nodes added for routing purposes but do not perform any processing.…”
Section: The Convolutional Snnmentioning
confidence: 99%
“…It is frequently cited that SNN hardware accelerators inherit the remarkable fault-tolerance capabilities of the biological brain, offering resilience to hardware-level faults induced by manufacturing defects, reduced-voltage memory operations, radiation, and aging. However, this assumption has been proven false according to recent fault injection experiments [6]- [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation